Penerapan Metode Weighted Product Untuk Menentukan Petugas Avsec Terbaik Pada PT. Angkasa Pura II Kualanamu - Bunga Ncari Putri Lea; R. Mahdalena Simanjorang (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
PT. Angkasa Pura II Kualanamu is still experiencing problems at this time, where the system for selecting the best Avsec officers has not reached the target and is currently not running optimally, all because the assessment of the selection of the best Avsec officers is still carried out manually / objectively. The system is designed to produce information that can help personnel managers to assess employee performance using data and models to solve problems using the Weighted Product (WP) method. The system development method used in this research is a waterfall which consists of needs analysis, system design using UML, a system designed to produce information that can help PT. Angkasa Pura II Kualanamu to assess the best Avsec officers by using data and models to solve problems using the Weighted Product (WP) method. The assessment is based on the criteria of achievement, performance, discipline, loyalty and responsibility.